A spectacle retained acrylic orbital prosthesis for rehabilitation of an exenterated eye - Parajuli, P K; Suwal, P; Singh, R K (Health Renaissance, 2012)
Exenteration of an eye causes massive disfigurement and psychologic as well as social embarrassment as facial appearance is severely crippled. Prosthetic rehabilitation of such patients, if done meticulously, will improve the appearance as well as their self confidence. This case report describes an orbital prosthesis fabricated to rehabilitate a patient with exenteration of right eye, with the most economical material and easily available technique. DOI: http://dx.doi.org/10.3126/hren.v10i2.6585 Health Renaissance 2012; Vol 10 (No.2); 144-146